Tm3+/Yb3+:NaGdF4 nanoparticles decorated g-C3N4/BiOBr0.75I0.25 multicomponent heterostructure: Structural, optical properties and UV–Visible-NIR responsive photocatalytic degradation of Rhodamine B and reduction of Cr(VI) - Sharma M.; Mishra J.N.; Singh S.; Singh P.; Singh S.K.; Singh P. (My University, 2025)
A wide solar spectral range responsive multicomponent heterostructure photocatalyst NGT/g-C3N4/BiOBr0.75I0.25 was successfully synthesized and used for the UV–visible-NIR photodegradation of the dye Rhodamine B and photoreduction of highly toxic hexavalent chromium ions. Our study shows that the heterostructure overcomes the drawbacks of limited visible-light absorption and fast charge recombination of g-C3N4. Herein, the incorporation of BiOBr0.75I0.25 extends the absorption in the visible region and endorses the separation rate of photogenerated charge carriers. Additionally, the upconversion nanoparticles NaGdF4: Tm/Yb (NGT) with its higher infrared light absorption capacity and characteristic emission spectral overlapping with absorption range of g-C3N4/BiOBr0.75I0.25 nanocomposite, further facilitates the photocatalytic activity of the NGT/g-C3N4/BiOBr0.75I0.25 heterostructured nanocomposite. Extensive structural, morphological, and compositional analysis was done using XRD, TEM, SEM, FE-SEM, XPS, and FTIR measurements. The PL emission, time-resolved decay, and electrochemical impedance spectroscopy were used to probe the separation rate of photogenerated electron-hole pairs and efficient energy transfer in NGT/g-C3N4/BiOBr0.75I0.25 heterostructured nanocomposite. The possible photocatalytic degradation mechanism was comprehensively proposed through a combination of UV–Vis absorption, Mott Schottky, and scavenger test analysis. The photodegradation efficiency of the heterojunction was 98 %, which is much higher than the bare g-C3N4 (74 %). Moreover, the heterostructure exhibited excellent long-term reusability, maintaining the photodegradation efficiency of 97.02 % even after four consecutive degradation cycles, establishing it as a preferable material for photocatalytic dye degradation. Additionally, NGT/g-C3N4/BiOBr0.75I0.25 heterostructured nanocomposite also demonstated better performance for the photoreduction of Cr(VI) to Cr(III), achieving photocatalytic efficiency of 98.86 % under acidic condition. © 2024 Elsevier Ltd